2018
DOI: 10.1002/pbc.27022
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea (hydroxycarbamide) genotoxicity in pediatric patients with sickle cell disease

Abstract: SCD increases, slightly but significantly, DNA damage in lymphocytes from patients with SCD. Patients with SCD treated with HU do not present more nucleoid damage than patients with SCD not treated with HU. Good responders to the HU treatment have significantly less nucleoid damage than poor responders. HU treatment at ≤30 mg/kg/day does not expose patients to a genotoxic plasma concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
10
0
3
Order By: Relevance
“…Friedrisch et al, 14 used the comet assay to analyze peripheral blood leukocytes of 28 patients with SCD treated with HU, and of 28 individuals without SCD, and they found higher levels of DNA damage in the group of patients treated with HU. Nevertheless, in this study by Friedrisch et al, 14 it is not possible to distinguish if the effects observed result from exposure to HU or due to the disease itself, as suggested by Rodriguez et al, 7 Moreover, another study presented with data in reference to 293 blood samples of 105 children, in a median of 2 years of HU therapy, in which the exposure to the drug was associated with significantly increased frequencies of MN in reticulocytes, reflecting the chromosome damage that occurred in the erythroblasts. 15…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…Friedrisch et al, 14 used the comet assay to analyze peripheral blood leukocytes of 28 patients with SCD treated with HU, and of 28 individuals without SCD, and they found higher levels of DNA damage in the group of patients treated with HU. Nevertheless, in this study by Friedrisch et al, 14 it is not possible to distinguish if the effects observed result from exposure to HU or due to the disease itself, as suggested by Rodriguez et al, 7 Moreover, another study presented with data in reference to 293 blood samples of 105 children, in a median of 2 years of HU therapy, in which the exposure to the drug was associated with significantly increased frequencies of MN in reticulocytes, reflecting the chromosome damage that occurred in the erythroblasts. 15…”
Section: Discussionmentioning
confidence: 65%
“…Similar to our findings, some reports in literature indicated treatment conditions in which HU did not lead to induction of DNA damage. Rodriguez et al, 7 employed the comet assay and found no significant difference in DNA damage between patients with SCD, treated, or not, with HU, with doses ≤30mg/kg/day. Using the CBMN-cyt assay in lymphocytes, Maluf et al, 16 found a small increase in the number of MN in the group of patients treated with HU, which correlated with duration of treatment and the final HU dose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations